Impact of the warm summer 2015 on emergency hospital admissions in Switzerland - Martina S. Ragettli; Ana M. Vicedo-Cabrera; Benjamin Flückiger; Martin Röösli (BMC, 2019)
Abstract Background Only a few studies have examined the impact of a particular heat event on morbidity. The aim of this study was to evaluate the impact of the warm summer 2015 on emergency hospital admissions (EHA) in Switzerland. The summer 2015 ranks as the second hottest after 2003 in the history of temperature observation in Switzerland. Methods Daily counts of EHA for various disease categories during summer 2015 were analyzed in relation to previous summers in Switzerland. Excess EHA for non-external causes during summer 2015 (June-August) were estimated by age group, gender, geographic region and disease category by comparing observed and expected cases. The latter were predicted from strata-specific quasi-Poisson regression models fitted to the daily counts of EHA for years 2012-2014. Results Over the three summer months in 2015, an estimated 2.4% (95% confidence interval [CI] 1.6-3.2%) increase in EHA (non-external causes) occurred corresponding to 2,768 excess cases. Highest excess EHA estimates were found in the warmest regions (Ticino [8.4%, 95% CI 5.1-11.7%] and the Lake Geneva region [4.8%, 95% CI 3.0-6.7%]) and among the elderly population aged ≥75 years (5.1%, 95% CI 3.7-6.5%). Increased EHA during days with most extreme temperatures were observed for influenza and pneumonia, certain infectious diseases and diseases of the genitourinary system. Conclusions Summer 2015 had a considerable impact on EHA in Switzerland. The daily number of EHA mainly increased due to diseases not commonly linked to heat-related mortality. No excess morbidity was found for cardiovascular and most respiratory diseases. This suggests that current public health interventions should be reevaluated to prevent both heat-related illness and deaths.